2006
DOI: 10.1016/j.fusengdes.2005.06.352
|View full text |Cite
|
Sign up to set email alerts
|

Physics basis for the advanced tokamak fusion power plant, ARIES-AT

Abstract: The advanced tokamak is considered as the basis for a fusion power plant. The ARIES-AT design has an aspect ratio of A ≡ R/a = 4.0, an elongation and triangularity of κ = 2.17, δ = 0.84 (evaluated at the separatrix surface), a toroidal beta of β = 9.2% (normalized to the vacuum toroidal field on at the plasma center), which corresponds to a normalized beta of β N ≡ 100 × β/(I P (M A)/a(m)B(T )) = 5.4. These beta values are chosen to be 10% below the ideal MHD stability limit. The bootstrap-current fraction is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 58 publications
1
25
0
Order By: Relevance
“…131 In DIII-D experiments with n ¼ 1 feedback stabilization, strong n ¼ 2 and n ¼ 3 contributions have been seen during instabilities, 179 suggesting coupling to higher toroidal modes. ITER's steady state scenario is expected to be near or above the no-wall stability limit for several toroidal mode numbers greater than unity 94 as are advanced power plant designs such as ARIES-AT 180 and DEMO. 181 However, to date very little is known about the passive stability of resistive wall modes with n > 1, and virtually no tokamak experiments have explored active stabilization with n > 1.…”
Section: E Feedback: Discussion and Challengesmentioning
confidence: 99%
“…131 In DIII-D experiments with n ¼ 1 feedback stabilization, strong n ¼ 2 and n ¼ 3 contributions have been seen during instabilities, 179 suggesting coupling to higher toroidal modes. ITER's steady state scenario is expected to be near or above the no-wall stability limit for several toroidal mode numbers greater than unity 94 as are advanced power plant designs such as ARIES-AT 180 and DEMO. 181 However, to date very little is known about the passive stability of resistive wall modes with n > 1, and virtually no tokamak experiments have explored active stabilization with n > 1.…”
Section: E Feedback: Discussion and Challengesmentioning
confidence: 99%
“…Use of these quasilinear models includes both full reactor design studies (e.g. ; Wenninger et al (2015); Jardin et al (2006)) and efforts to predict and optimise performance for particular devices (e.g. Mukhovatov et al (2003); Budny (2009); Kinsey et al (2011); Parail et al (2013); Meneghini et al (2016)).…”
Section: Introductionmentioning
confidence: 99%
“…However, even where designs are based on extrapolation from the best performing experimental configurations, using the most complete reduced models available at the time (e.g. Jardin et al (2006)), the designs can know nothing of potential new phenomena, leading to possible further gains, that might exist in the vast configuration space at their disposal (more than two decades ago, Galambos et al (1995) showed that in theory, where full control could be maintained over turbulent transport, it was possible to reduce the capital cost of the reactor plant by 30%, that is, 10 billion (1995) US dollars, compared to the most advanced designs of the day). This still-largelyuncharted configuration space is best explored in conjunction with nonlinear models, since any exploration by reduced models could conceivably miss a crucial physics effect not yet included within the model ‡ (c.f work in the stellarator community which clearly † In stating this we have not overlooked the important work across the entire field (which a lack of space prevents us from surveying) studying the performance of and possible improvements to existing designs such as ITER and DEMO using nonlinear simulations.…”
Section: Introductionmentioning
confidence: 99%
“…[10].) Locally reversed magnetic shear is most commonly produced naturally by squeezing the field lines at high pressure, creating the so-called "second stability" regime, which was first predicted by ideal magnetohydrodynamic (MHD) theory [11] and provides the basis behind the design of advanced tokamak [12] and spherical torus [13] configurations. However, locally reversed magnetic shear can also be produced by changing the plasma shape, such as varying the elongation and triangularity, since this changes the poloidal magnetic field.…”
Section: Introductionmentioning
confidence: 99%